2004
DOI: 10.1242/jeb.01106
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of neuronal KATP channels in brain hypoxia

Abstract: SUMMARY During severe arterial hypoxia leading to brain anoxia, most mammalian neurons undergo a massive depolarisation terminating in cell death. However,some neurons of the adult brain and most immature nervous structures tolerate extended periods of hypoxia–anoxia. An understanding of the mechanisms underlying this tolerance to oxygen depletion is pivotal for developing strategies to protect the brain from consequences of hypoxic-ischemic insults. ATP-sensitive K+ (KATP) channels are good sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
2
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 78 publications
0
98
2
3
Order By: Relevance
“…Changes in metabolic state or intracellular Ca 2þ concentration after ischemia can modulate a variety of K þ channels, including K ATP channels, Ca 2þ -activated large conductance K þ channels, and delayed rectifier voltage-dependent K þ channels (7,80,106). Recent evidence has shown that sublethal ischemic injury is associated with a protein-phosphatase 2B (PP2B or calcineurin)-dependent dephosphorylation of existing Kv2.1 channels, which is accompanied by a dispersal of somatodendritic Kv2.1 clusters and hyperpolarizing shifts in voltage-dependency (80).…”
Section: Preconditioning Triggers Zinc-regulated Gene Expressionmentioning
confidence: 99%
“…Changes in metabolic state or intracellular Ca 2þ concentration after ischemia can modulate a variety of K þ channels, including K ATP channels, Ca 2þ -activated large conductance K þ channels, and delayed rectifier voltage-dependent K þ channels (7,80,106). Recent evidence has shown that sublethal ischemic injury is associated with a protein-phosphatase 2B (PP2B or calcineurin)-dependent dephosphorylation of existing Kv2.1 channels, which is accompanied by a dispersal of somatodendritic Kv2.1 clusters and hyperpolarizing shifts in voltage-dependency (80).…”
Section: Preconditioning Triggers Zinc-regulated Gene Expressionmentioning
confidence: 99%
“…However, different neurons have distinct immediate and long-term protective mechanisms "on demand" to suppress the hyperexcitability induced by brief hypoxia/ischemia. One immediate mechanism is the depression of neuronal excitability during hypoxia/ischemia-induced activation of neuronal K ATP channels (Ballanyi, 2004), especially in neurons in anoxia-tolerant brain regions such as substantia nigra pars reticulata (Yamada et al, 2001), dorsal vagal neurons, and cerebellar Purkinje cells (Ballanyi, 2004). However, many brain neurons (e.g., hippocampal pyramidal neurons) express lower levels of functional K ATP channels (Zawar and Neumcke, 2000;Griesemer et al, 2002), such that brief hypoxia and ischemia in hippocampal slices induces immediate seizure-like hyperactivity followed by a delayed and prolonged suppression of neuronal activity (Kawasaki et al, 1990;Yamamoto et al, 1997).…”
Section: Potential Roles For Kv21 Modulation In Brain Ischemiamentioning
confidence: 99%
“…Conversely, the neuroprotective potential of K ATP channel activation by agents such as diazoxide has also been demonstrated in animal models of brain ischemia (Ballanyi, 2004). It has been hypothesized that alterations in cellular redox status and generation of reactive oxygen species (ROS) elicit preconditioning by contributing to the opening of K ATP channels within the mitochondria (Avshalumov and Rice, 2003).…”
Section: The Clinical Realities Of Diabetes and Ischemia Vulnerabilitymentioning
confidence: 99%